Spatial Orientation of Galaxies in the SDSS DR7 Supercluster - Malla, Janak Ratna (Academia Research Journal, 2024)
Spatial orientations of spin vectors 1423 galaxies in the SDSS DR7 Supercluster S[239+016+0037] was studied. The database of these galaxies is taken from the SDSS DR7 data release. Our main goal is to find out the angular momentum vectors of galaxies in the Supercluster S[239+016+0037]. Random simulation method is used to remove selection effects from the database. Finally, three statistics to compare the differences between theoretical and observed distributions: chi-square, auto-correlation, and the Fourier test. All these statistical tests suggest the random orientation of galaxies in the SDSS DR 7 Supercluster S[239+016+0037]. Furthermore, the evolution of the galaxies in the Supercluster supports the hierarchy model as suggested by Peebles (1969).